Unraveling historical genetic divergence and gene flow patterns between island (Taiwan) and mainland (China) of Fagus hayatae - Suhardi, Rizal M.; Ju, Li-Ping; Hsu, Tsai-Wen; Chen, Tze-Ying; Shih, Huei-Chuan; Zhang, Zhi-Yong; Ko, Ya-Zhu; Shiao, Meng-Shin; Chiang, Yu-Chung (Frontiers in Plant Science, 2025)
The disjunctive distribution of Fagus hayatae between Taiwan and mainland China provides a unique framework for understanding phylogeographic patterns and evolutionary processes in relict tree species. This study investigated the genetic diversity, population structure, and phylogeographic history of F. hayatae using microsatellite and chloroplast DNA markers. Analysis of 249 samples from nine populations revealed that Taiwanese populations possess higher genetic diversity with significant inbreeding, while mainland Chinese populations showed lower diversity and inbreeding levels. Chloroplast DNA analysis identified eight haplotypes, with unique variants in Taiwanese populations. AMOVA confirmed significant genetic differentiation between the two regions, revealing four distinct clustering patterns and three clear phylogenetic clades, including an early-diverging Taiwanese TS population. Molecular divergence time estimation based on chloroplast DNA sequences indicates a temporal divergence pattern within F. hayatae populations, with the Taiwanese TS lineage exhibiting an earlier separation event, followed by subsequent divergence between other Taiwanese populations (PCTS and AW) and mainland Chinese populations (CH). These phylogeographic events temporally correspond with significant paleoclimatic and geotectonic episodes in East Asia. Demographic and historical biogeography inference revealed a recent population decline in Taiwan, in contrast to more stable population dynamics on the mainland, while historical gene flow between the regions remains limited, and suggested several dispersals and vicariant events influencing the current genetic structure. These findings not only delineate the genetic structure shaped by historical geographic isolation and contemporary evolutionary processes but also emphasize Taiwan’s role as a genetic refugium for F. hayatae.